Exploring Teachers and Students’ Perceptions of Task-Based Instruction in Teaching English Speaking - Mukammal, Mukammal; Hafiz, Hairori Sahrul; Terasne, Terasne (LPPM Universitas Bumigora Mataram, 2025)
Task-Based Instruction (TBI) emphasizes meaningful tasks to promote students’ language use, especially in speaking. This research aims at exploring the implementation of Task-Based Instruction in teaching speaking at Madrasah Aliyah (MA) Darunnashihin Nahdlatul Wathan (NW) Ranggagata. The research used a qualitative descriptive method, with interviews as the primary data collection instrument. The participants in this study are an English teacher and several tenth-grade students. The data are analyzed descriptively based on the responses from the interview. The findings showed that Task-Based Instruction helped students become more engaged and confident in speaking English. The teacher also stated that TBI encouraged more student-centered learning and meaningful communication in the classroom. However, some challenges, such as time management and students’ varying speaking proficiency, were also identified. In conclusion, Task-Based Instruction is considered effective and beneficial in supporting students’ speaking development.